The histiocytosis Erdheim–Chester disease is an inflammatory myeloid neoplasm. (September 2015) - Haroche, Julien; Cohen-Aubart, Fleur; Charlotte, Frédéric; Maksud, Philippe; Grenier, Philippe A; Cluzel, Philippe; Mathian, Alexis; Emile, Jean-François; Amoura, Zahir
Abstract : Erdheim–Chester disease (ECD) is a rare, non-Langerhans histiocytosis, characterized by the infiltration of tissues by foamy CD68 + CD1a − histiocytes. 99 Technetium bone scintigraphy revealing almost constant tracer uptake by the long bones is highly suggestive of ECD, and a 'hairy kidney' appearance on abdominal computed tomography scan is observed in about half of all ECD cases. CNS involvement is a strong prognostic factor and independent predictor of death. IFN-α seems to be the best initial treatment for ECD. More than half of all ECD patients carry the BRAF V600E mutation. More than 30 patients worldwide harboring this mutation and displaying multisystemic, refractory ECD have been treated with vemurafenib, a BRAF inhibitor, which has proven highly beneficial. Other recurrent mutations of the MAPK and PIK3 pathways ( NRAS, PIK3CA ) have recently been described. These mutations should lead to a new classification of histiocytic disorders such that Langerhans cell histiocytosis and ECD are classified as inflammatory myeloid neoplasms.